Making Qualitative Interviews in Music Therapy Research More Accessible for Participants Living With Dementia – Reflections on Development and Implementation of Interview Guidelines. (14th September 2021) - Thompson, Zara; Baker, Felicity Anne; Clark, Imogen Nicola; Tamplin, Jeanette
Purpose. This paper reports findings from a project that sought to develop accessible guidelines for including people with dementia in qualitative interviews in a music therapy study, based on experience from people previously involved in qualitative music therapy research. Method. People with previous experience of qualitative music therapy research were invited to participate in semi-structured interviews about how the interview process could be made more accessible. Participants included four family-caregivers and three music therapy-researchers. Interview data were analysed using thematic analysis. Findings were used to develop guidelines for a subsequent study; reflections on the implementation of these guidelines are provided. Results. Five themes were identified: (a) motivators and barriers to participating in interviews; (b) pragmatic elements that impact interview participation; (c) relationship dynamics may impact the interview; (d) familiarity fosters comfort, enables preparation and support and (e) broader considerations for accessible research design. Conclusions. Themes identified align with reports from the extant literature. Reflections on implementation of the guidelines reveal the need for more clarity around the ethics of building rapport in qualitative research. Implications about future uses of the guidelines, including the use of music as a research tool are discussed.